Ozonated Aloe Vera Oil Accelerates Radiation Dermatitis Healing in Sprague Dawley Rats - Yan Prajoko; Chandra Manapa; Tsamara Nugroho (Middle East Journal of Cancer)
Background: Radiation dermatitis is the most common side-effect of radiation therapy. The current daily therapy uses topical corticosteroids to reduce inflammation. However, long-term usage may cause some side-effects. Aloe vera could act as an anti-inflammatory and antioxidant agent, and ozone exhibits an antioxidant dan bactericidal effect. The present study aimed to analyze the effect of topical administration of ozonated Aloe vera oil on inflammatory and growth factors in radiation dermatitis wounds.Method: This was an experimental study with a "post-test only control group” design. A total number of 36 Sprague Dawley rats were divided into two control and four intervention groups. C1: no intervention, C2: hydrocortisone ointment, P1: Aloe vera oil, P2/P3/P4: ozonated Aloe vera oil 300/600/1200 mg/ml. Termination and histopathological analysis of inflammatory and growth factors were performed after seven days of treatment. Statistical analysis was performed using SPSS version 22 (IBM corporation, USA). The normality test of the data was carried out using the Sapphiro Wilk test. Normally distributed data were subjected to the One-Way ANOVA test and continued with the Post Hoc LSD test after a significant difference was obtained. Data that were not normally distributed were tested using the Kruskal-Wallis test, followed by the Mann-Whitney U test. Therefore, all values obtained were considered significant at P < 0.05.Results: Significant differences were found between the control and the treatment groups. Decreased tumor necrosis factor-alpha expression, neutrophil infiltration, endothelial damage, and increased tumor growth factor beta, platelet-derived growth factor, and fibroblast count were seen after seven days of intervention.Conclusion: Ozonated Aloe vera oil can accelerate wound healing of radiation dermatitis.